Bone mineral density in African–American women with symptomatic uterine leiomyoma. (September 2010) - Muneyyirci-Delale, Ozgul; Nessim, Fiby; Mathur, Deepali; Osei-Tutu, Nanna; Karam, Jocelyne; Parris, Rudolph; McFarlane, Samy I
Objective: Uterine leiomyoma is associated with increased BMD in Caucasian women and is largely attributed to the state of hyperestrogenemia associated with disease. This relationship, however, has not been previously described in African–American women. We aim to assess BMD in African–American women with symptomatic uterine leiomyoma.Design: Case–control study. Materials & methods: 29 African–American women with uterine leiomyoma signed an Institutional Review Board (IRB) approved consent form at a reproductive clinic of an inner city hospital in Brooklyn, NY, USA. BMD and T-score of lumbar spine was compared with a controlled group matched for age, race and BMI. BMD of lumbar spine was measured using Hologic QDR 4200 in both groups. Data are presented as mean ± SEM.Results: For the entire study population the mean age (years) was 42.07 ± 1.15, and the BMI (kg/m 2 ) was 29.37 ± 0.93 in patients with uterine leiomyoma and 30.07 ± 1.06 for the control group (p = 0.07). There was a significant difference in the mean BMD (cm 2 ) between the uterine leiomyoma group (1.17 ± 0.03) compared with control (1.05 ± 0.02 p < 0.01). The T-score for the uterine leiomyoma group was significantly higher compared with the control group (0.31 ± 0.25 and -0.74 ± 0.21 with p < 0.01). The prevalence of osteopenia (T-score <-1) was lower for the leiomyoma group when compared with controls, (p < 0.02).Conclusion: Consistent with data from the white population with uterine leiomyoma, our data showed a significantly higher BMD in African–American women with uterine leiomyoma, compared with an age- and race-matched cohort. The implications of these findings remain to be investigated and further confirmed in future longitudinal studies.